Prevalence of thyroid dysfunction and effect of contrast medium on thyroid metabolism in cardiac patients undergoing coronary angiography. (February 2013) - Marraccini, Paolo; Bianchi, Massimiliano; Bottoni, Antonio; Mazzarisi, Alessandro; Coceani, Michele; Molinaro, Sabrina; Lorenzoni, Valentina; Landi, Patrizia; Iervasi, Giorgio
Background: Iodinated contrast media (CM) may influence thyroid function. Precautions are generally taken in patients with hyperthyroidism, even if subclinical, whereas the risks in patients with hypothyroidism or low triiodothyronine (T3) syndrome are not considered as appreciable. Purpose: To assess the presence and type of thyroid dysfunction in patients admitted for coronary angiography (CA), to assess the concentration of free-iodide in five non-ionic CM, and to evaluate changes in thyroid function after CA in patients with low T3 syndrome. Material and Methods: We measured free T3, free thyroxine (T4), and thyroid-stimulating hormone (TSH) in 1752 consecutive patients prior to CA and free-iodide in five non-ionic CM. Urinary free-iodide before and 24 h after CA, and thyroid hormone profile 48 h after CA were also made in 17 patients with low T3 syndrome. Patients were followed up for an average duration of 63.5 months. Results: The patients were divided into four groups: euthyroidism (60%), low T3 syndrome (28%), hypothyroidism (10%), and hyperthyroidism (2%). The free-iodide resulted far below the recommended limit of 50 μg/mL in all tested CM. In low T3 syndrome, 24-h free-iodide increased after CA from 99.9± 63 ug to 12276±9285 ug (P< 0.0001). A reduction in TSH (4.97±1.1 vs. 4.17±1.1 mUI/mL, P < 0.01) and free T3 (1.44±0.2 vs. 1.25±0.3 pg/mL, P < 0.01), with an increase in free T4 (11.3±2.9 vs. 12.5±3.4 pg/dL, P < 0.001), was found. Patients with functional thyroid disease in the follow-up had a significant lower rate survival compared to euthyroid patients (90.7 vs. 82.2%, P < 0.00001). Conclusion: Thyroid dysfunction is frequent in patients who perform a CA, and low T3 syndrome is the predominant feature. The administration of contrast medium may further compromise the thyroid function.